Suprimento arterial da glândula tireoide em coelhos da raça Nova Zelândia - Borges, Ana Paula Silva (2017)
The objective was to describe the topography, microscopy and arterial irrigation of the thyroid gland. Thirty male specimens of New Zealand rabbits (Oryctolagus cuniculus) were used. The arterial system was marked by cannulation of the thoracic aorta and fixed in aqueous 10% formaldehyde solution.The light microscopy technique was performed in the Laboratory of Histology, Cell Biology and Embryology (DBHEM / ICBIM / UFU), and was collected from three rabbits, the isthmus, the right and left lobes of the gland, following the usual histological routine , and the slides were stained with Hematoxylin / Eosin. The thyroid gland consists of two flat, elongated lobes located ventrolateral to the trachea. Topographically there is a close relationship of the gland to the lateral surfaces of the first five tracheal rings, immediately caudal to the cricoid cartilage and medially to the right and left common carotid arteries. The arterial supply of the thyroid gland in both antimer is performed by the thyroid artery which is a branch of the common carotid artery. After its origin at the level of the first tracheal ring the thyroid artery continues in a caudocranial path, reaches the cranial part of the thyroid gland divides into several branches that distribute themselves in this organ. The histological sections revealed that the cellular aspect of the isthmus region maintains the same organization and the same characteristics observed in the thyroid lobes. The thyroid gland in Oryctolagus cuniculus is small, consisting of two bilateral lobes united by an isthmus that presents glandular tissue.